Solar Wind Drivers of Auroral Omega Bands - V. Cribb; T. I. Pulkkinen; L. Kepko; B. Gallardo‐Lacourt; E. Donovan (Geophysical Research Letters, 2024)
Abstract Omega bands are mesoscale auroral structures emerging as eastward moving quasi‐periodic poleward protrusions well within the closed field line region of the auroral oval. Neither specific conditions of their appearance nor their causes are well understood. We perform a superposed epoch analysis of OMNI and SuperMAG measurements taken during 28 omega band events recorded by auroral all‐sky imager observations from 2006 to 2013 to identify their solar wind drivers. We find local enhancements in the solar wind flow speed, magnetic field, pressure, and proton density at the time of the omega band observation. In the magnetosphere‐ionosphere, we see enhancements in the ring current, partial ring current, and auroral electrojets. These features are consistent with geomagnetic activity caused by stream interaction regions (SIRs). 19 of our events overlap with SIRs from published event catalogs. Our findings suggest that omega bands are driven by compression regions commonly associated with SIR events.